KOLEKSI DAN KARAKTERISASI KARAKTER KUALITATIF 4 AKSESI LOKAL TANAMAN GAMBAS (Luffa acutangula L.) - Yonita Sholihatun Nisa; Rahmi Sri Sayekti (Agrotechnology Innovation (Agrinova), 2020)
Ridge gourd (Luffa acutangula L.) is a widely growing vegetative climber and used as a vegetable and traditional medicine. Ridge gourd is cross-pollinated crop and most of them are monoecious so that the description of the plants owned by each luffa accession is different. This study aims to determine the diversity between luffa accessions from different regions. The accessions used in this study were CB-LF 35, CB-LF 78, CB-LF 79, and CB-LF 98. The design used in this study was a Completely Randomized Design (CRD) with 4 luffa accessions as a treatment and 10 individuals from each of them as a replication. Observation of morphological characterization was carried out by observing qualitative character including plant vigor, stem shape, presence of tendrils, leaf color, leaf pubescense density, leaf shape, leaf lobes, and leaf edge. The morphological data obtained then compared between one accession to another accession. The results showed that the accessions of CB-LF 35, CB-LF 78, CB-LF 79 and CB-LF 98 had plant strength characters which were categorized as strong, angular stem shape, tendrils, green leaf color, a lot of trichome density, shape of the leaf are liver, and leaf lobe are classified into deep categories. The difference in character occurred in the leaf edge character with CB-LF 79 accession which had a toothed leaf edge character which are different from the other accessions namely CB-LF 35, CB-LF 78 and CB-LF 98 which had smooth leaf edge characters.